NaF treatment increases TNF-alpha and resistin concentrations and reduces insulin signal in rats - Chiba, Fernando Yamamoto [UNESP]; Colombo, Natalia Helena [UNESP]; Shirakashi, Daisy Jaqueline [UNESP]; da Silva, Viviane Clicie [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Silva, Cristina Antoniali [UNESP]; Sumida, Doris Hissako [UNESP] (Elsevier B.V. Sa, 2012)
The use of fluoridated products has significantly contributed to the reduction in rates of dental caries. However, excessive sodium fluoride (NaF) intake promotes inhibition of glycolysis, decrease in insulin secretion, hyperglycemia, and insulin resistance. Seven-week-old castrated male Wistar rats were used to evaluate the chronic effect of NaF on insulin sensitivity, insulin signal transduction in white adipose tissue (WAT), and plasma TNF-alpha and resistin concentrations. The animals were randomly divided into two groups: (1) control group (CN); (2) fluoride (F) group, which was treated with NaF in the drinking water and F in the food pellets (estimated total F intake: 4.0 mg/kg bw/day). After 42 days, an intravenous insulin tolerance test (0.75 U/kg), plasma TNF-alpha and resistin quantification analysis, and insulin receptor substrate (pp185 - IRS-1/IRS-2) tyrosine phosphorylation and IRS-1 serine phosphorylation status tests in WAT were performed. The chronic treatment with F promoted: (1) decrease in pp185 (IRS-1/IRS-2) tyrosine phosphorylation status in the WAT; (2) increase in IRS-1 serine phosphorylation status in the WAT; (3) increase in plasma concentrations of TNF-alpha and resistin; and (4) decrease in insulin sensitivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorine; Insulin receptor substrate proteins; Diabetes mellitus; Insulin resistance; Fluorides